แนวทางการจัดการเรียนการสอนศิลปะที่ส่งเสริมการเห็นคุณค่าในพหุวัฒนธรรม ระดับประถมศึกษาในโรงเรียนนานาชาติ - มณีพฤกษ์ ณัฐชนา; พลประเสริฐ อภิชาติ (An Online Journal of Education, 2018)
The objectives of this research were to 1) study art education instruction to promote multicultural values in elementary international schools , and 2) propose guidelines for art education instruction to promote multicultural values in elementary international school. The sample groups were 5 art teachers and 80 students from 4 international schools from 4 international education systems in Thailand. The research instruments consisted of 1) curriculum analysis form, 2) observation of art class form, 3) art teacher interview form 4) student interview form, and 5) curriculum evaluation form for experts. The data were analyzed using by descriptive statistics Means, frequencies, standard deviation, and content analysis. The findings revealed that 1) art curriculums contents reflect on culture. There were extracurricular activities to focus on culture, integration between content of art and culture, art instruction media represent to culture, and many types of evaluation methods. 2) guidelines for art education instruction to promote multicultural values in elementary schools were as follows: curriculum should be contributing to multicultural, contents were defined in accordance with social context and cultures by teaching and learning to understand the concepts and express them individually. These guidelines emphasis on encouraging students to develop artistic and creative skills alongside culture experiences and good attitudes towards living in multicultural societies. Evaluation methods were artwork, explaining concept, participation in classroom, and criticism. The result of assessment of guidelines for art education instruction to promote multicultural values in elementary international schools by experts was appropriate and applicable with highest level.